O papel do hipocampo na memória operacional em pacientes com epilepsia do lobo temporal mesial após corticoamigdalohipocampectomia - Tudesco, Ivanda de Souza Silva [UNIFESP] (2014)
Previous studies suggest that, in addition to being a critical structure for formation and retrieval of episodic memory, the hippocampus, also contributes to the functioning of the working memory. To investigate this subject, the present study researched the performance in several tasks in working memory considering the multiple-components model of Baddeley and Hitch (1974) and Baddeley (2000) in tasks that require intense participation of the episodic buffer (working memory capacity tasks: operation wordspan, counting span and Brown-Peterson), phonological loop (digit span), visuospatial sketchpad (Corsi block-tapping task) and the central executive (Random Number Generation) in patients with unilateral mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) post-surgery to control seizures – left or right corticoamygdalohippocampectomy (L-CAH or R-CAH). Episodic memory was assessed through tests of logical memory, verbal paired associates, Rey complex figure and visual reproduction; to measure verbal fluency phonological (FAS) and semantic (Animals category) were used. We studied 60 individuals: 20 patients underwent L-CAH, R-CAH and and 20 healthy subjects to the control group were matched. The results showed that patients with MTLE-HS after L-CAH and R-CAHD had impairment in verbal and non-verbal episodic memory as well as in phonological fluency as expected. As for working memory and its subcomponents, patients that underwent L-CAH demonstrated impairment only to operation word-span, but not in other tasks as counting-span and Brown-Peterson. On the task that requires the central executive, patients in both groups showed consistent performance similar to the control group. It is suggested that only the left hippocampus, after resection, affects the capacity of working memory when the amount of verbal material to be held temporarily exceed the capacity of the short-term memory. However, this impairment is independent of the severe episodic memory deficit observed in these patients.